Analisis Metabarcoding ITS Plastifer dari Tempat Pembuangan Akhir Bukit Meusara Jantho Aceh Besar: Upaya Mitigasi Orangutan Sumatra (Pongo abelii) dari Risiko Cemaran Mikroplastik - Napisyah, Pingkan; Lubis, Syafrina Sari (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify the diversity of plastic-colonizing fungi (plastisphere) at the Bukit Meusara Landfill in Jantho, Aceh Besar, located 5-8 km from the Sumatran Orangutan (Pongo abelii) rehabilitation center, using a metabarcoding approach with the Nanopore platform. Analysis results revealed 143 OTUs from 81,414 sequences with a Shannon index of 2.77, indicating high fungal diversity in the plastisphere. The fungal community was dominated by Ascomycota (83.2%), particularly the class Sordariomycetes (51.7%). Dominant species included Mycothermus thermophilus (9-10%), M. thermophiloides (6%), Brocchiosphaera bulbiformis (5%), and Thermomyces lanuginosus (4%). The identified thermophilic fungi are known to produce enzymes such as laccase, cutinase, lignin peroxidase, and manganese peroxidase, which have potential for degrading PET, PS plastics, and biodegradable polymers. This study provides baseline data on indigenous plastisphere diversity that can be developed as a bioremediation consortium for mitigating microplastic pollution in Sumatran orangutan conservation areas.